2019
DOI: 10.1016/j.immuni.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor PU.1 Promotes Conventional Dendritic Cell Identity and Function via Induction of Transcriptional Regulator DC-SCRIPT

Abstract: Graphical Abstract Highlights d PU.1 is required for conventional dendritic cell (cDC) formation and function d PU.1 represses plasmacytoid DC differentiation d DC-SCRIPT (Zfp366) is a key transcriptional target of PU.1 d DC-SCRIPT is specifically expressed in cDCs and promotes cDC1 differentiation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 64 publications
(74 reference statements)
2
52
0
Order By: Relevance
“…They also found that the pioneer factors Cebpb and Hif1 were involved in inflammatory gene expression (TNF and ROS), whereas PU.1 led to their downregulation (96). The latter result was consistent with the recent finding by Chopin et al that PU.1 is involved in conventional dendritic-cell development (102). Next, they confirmed the known roles of Stat1/2 in the activation of the antiviral response and the roles of Rel, Irf2, and Atf3 in its suppression.…”
Section: Single-cell Screens With Crisprsupporting
confidence: 86%
“…They also found that the pioneer factors Cebpb and Hif1 were involved in inflammatory gene expression (TNF and ROS), whereas PU.1 led to their downregulation (96). The latter result was consistent with the recent finding by Chopin et al that PU.1 is involved in conventional dendritic-cell development (102). Next, they confirmed the known roles of Stat1/2 in the activation of the antiviral response and the roles of Rel, Irf2, and Atf3 in its suppression.…”
Section: Single-cell Screens With Crisprsupporting
confidence: 86%
“…Irf8 are expressed in cells that are further differentiated (36,37). This suggests that Flt3 high MPPs are less differentiation-prone than Flt3 mod MPPs.…”
Section: Resultsmentioning
confidence: 99%
“…2c , d ). Other factors impacting DC development such as Bcl11a, Spi1, Klf4 , and Notch2 29 , 30 , 31 , 32 were not differentially expressed across the CDP, perhaps suggesting that specification of cDC2s and pDCs occurs after the CDP ( Fig. 2d , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%